Study of Rheological Characteristics of Coal Water Alcohol Slurry - Routray, Anupama; Kumari Padhy, Mamata; K. Senapati, P.; Das, Debadutta (International Journal of Engineering and Technology, 2018)
A comparative analysis of coal water alcohol slurry (CWAS) has been done taking glycerol, glycol and ethanol as an additive.10 ml of alcohol additive was added to the slurry and a range of 50-64% of concentration by mass was obtained. Various parameters like shear rate, shear stress, pH, temperature, apparent viscosity, stability etc. has been examined and compared the result of coal water glycerol slurry, coal water glycol slurry and coal water ethanol slurry for a particular mono-modal sample. From each parameter study it is concluded that coal water alcohol slurry in presence of glycerol has less viscosity as well as more stability than coal water alcohol slurry in presence of glycol and ethanol. This is due to the presence of more number of OH- radicles in the alcohol group. More OH- radicles creates more carbon atoms which will increase the tendency to adsorb on the surface of coal.Â Â